Performance on MMSE sub-items and education level in presenilin-1 mutation carriers without dementia - Ringman, John M. (2007)
BACKGROUND: Spanish-language screening tests that are sensitive to the early cognitive changes of Alzheimer’s disease (AD) are needed. Persons known to be at 50% risk for young-onset AD due to presenilin-1 (PSEN1) mutations provide the opportunity to assess which measures on the Mini-mental State Examination (MMSE) are most sensitive to these early changes. METHODS: We performed genetic and Spanish-language cognitive testing on 50 Mexican persons without dementia at risk for inheriting PSEN1 mutations. We then compared the performance on sub-items of the MMSE between PSEN1 mutation carriers (MCs) and non-carriers (NCs) using t-tests and Fisher’s exact tests. Exploratory multiple logistic regression analyses were also performed. RESULTS: Twenty-nine persons were MCs and 21 NCs. NCs tended to achieve higher levels of education (p = 0.039) than did MCs. MCs tended to perform more poorly when spelling “MUNDO” backwards and on Orientation, particularly regarding the date. In multiple regression analyses the ability of backwards spelling to predict PSEN1 mutation status was reduced when education was included as an independent variable. CONCLUSION: Subjects in the earliest stage of PSEN1-related AD showed deficits on orientation to date and in divided attention when spelling backwards. It is unclear if educational level should be considered an associated feature or a confounding variable in this population although it should be taken into account when considering performance on the MMSE task of divided attention. The relative lack of deficits on delayed recall of three words probably represents the insensitivity of this measure in early AD. This study supports the utility of autosomal dominant AD as a model of the more common sporadic form of the disorder.